Wilderness in Mythology and Religion : Approaching Religious Spatialities, Cosmologies, and Ideas of Wild Nature. - Feldt, Laura (Religion and Society., 2012)
Wilderness mythology is one of the most abiding creations in the history of religions, and yet it has not previously been subject to scrutiny or theorizing from a cross-cultural, "study-of-religions perspective". This book addresses the need for cross-cultural anthropological and history of religions analyses by offering in-depth case studies of the use and functions of wilderness spaces in diverse religions. It offers new theoretical perspectives on the study of religious spatialities, cosmologies, and ideas of wild nature that challenge previous dichotomizing approaches.